Mental health benefits of mounted equine‐assisted therapies: A scoping review. (10th July 2022) - Ward, Jessica; Hovey, Angela; Brownlee, Keith
Abstract: Across mental health professionals, there is growing interest in the field of Equine‐Assisted Therapy (EAT). Preliminary evidence suggests EAT is beneficial for a wide spectrum of client populations. EAT programs may be based on groundwork alone, where participants interact with the horses from the ground only, or they may incorporate mounted activities. It remains unclear whether mounted activities add therapeutic benefits to the EAT experience for participants. This scoping review explored whether mounted activities, specifically where the client rides the horse, contribute to distinct therapeutic benefits. Nine databases were searched for studies of EAT programs that included horse riding as a central component of the therapeutic intervention and 36 studies were included in the analysis. The results of these studies suggest that mounted activities positively contribute to a variety of issues experienced by different client groups. However, further quality research is needed to carefully examine riding activities as an independent phenomenon, in order to establish what contribution‐mounted activities, over and above groundwork, make to any therapeutic benefit of the EAT experience.